Pendistribusian Masker Sebagai Alat Pencegahan Covid-19 di Kelurahan Mekarjaya, Kabupaten Bandung - Alifia Ayu Purwanto Putri (PT. Gyandharma Global Media, 2024)
Lack of public awareness of implementing health protocols has led to an increase in the number of Covid-19 cases, including in Mekarjaya Village, Bandung. One of the objectives of the Thematic KKN activities in Mekarjaya Village, Bandung is to distribute masks as an effort to prevent Covid-19. The methods used are Participatory Learning and Action and Participatory Rural Appraisal, then continued with information collection using the on-the-spot survey method. The results of the mask distribution activities by these students have increased the response and awareness of the community in Mekarjaya Village, Bandung in implementing health protocols.